A critical analysis of social development: features, definitions, dimensions and frameworks - Mohamed, Ali Ishag Adam; Mohammed, Mustafa Omar; Barom, Mohd Nizam (Canadian Center of Science and Education, 2019)
The concept of development has evolved over the past two centuries. The main idea of economic development expanded from economic growth to poverty alleviation, sustainable development, human development, Millennium Development Goals (MDGs), and Sustainable Development Goals (SDGs). Preliminary findings show that these concepts are mainly focused on the physical and material development, ignoring social development which is very fundamental to development. In recent years, the literatures have begun to emphasise that social development is an important dimension of development and its importance was confirmed globally after introducing SDGs. However, the findings in these works remain inconsistent to what constitutes social development, they lack consensus and clear definition of social development, they focus on the physical dimension of social development and, they emphasise on the physical dimension of social development frameworks. This study aims critically to examine the shortcomings and limitations of existing social development, along with its features, definitions and dimensions. The study also attempts to identify the shortcomings of social development frameworks, and to recommend the direction towards developing social development framework which will be more comprehensive in nature. The paper employs meta-analysis and content analysis methods through the review and analysis of related literature on development, especially social development.